2018
DOI: 10.1021/acs.biomac.8b01133
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-Targeted, Echogenic Polymersomes for Delivering a Cancer Stemness Inhibitor to Pancreatic Cancer Cells

Abstract: Chemotherapeutic agents for treating cancers show considerable side effects, toxicity, and drug resistance. To mitigate the problems, we designed nucleus-targeted, echogenic, stimuli-responsive polymeric vesicles (polymersomes) to transport and subsequently release the encapsulated anticancer drugs within the nuclei of pancreatic cancer cells. We synthesized an alkyne-dexamethasone derivative and conjugated it to N-polyethylene glycol (PEG)-polylactic acid (PLA) copolymer employing the Cu catalyzed "Click" rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Click chemistry is a product synthesis procedure that combines small modular units and is characterized by "green" one-pot synthesis conditions, high specificity, and high product yield, as well as minimal and non-toxic by-products [85]. Therefore, click reactions, including Cu(I)-catalyzed azide-alkyne cycloaddition and Cu(II)-catalyzed [3 + 2] azidealkyne cycloaddition, have been used for the synthesis of DEX conjugates [86][87][88][89][90].…”
Section: Click Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Click chemistry is a product synthesis procedure that combines small modular units and is characterized by "green" one-pot synthesis conditions, high specificity, and high product yield, as well as minimal and non-toxic by-products [85]. Therefore, click reactions, including Cu(I)-catalyzed azide-alkyne cycloaddition and Cu(II)-catalyzed [3 + 2] azidealkyne cycloaddition, have been used for the synthesis of DEX conjugates [86][87][88][89][90].…”
Section: Click Reactionsmentioning
confidence: 99%
“…An in vivo study comparing the conjugate to the equivalent dose of free DEX showed that a single administration of the DEX-PEG conjugate provided a long-term (>15 days) reduction in ankle joint inflammation in a rat model of adjuvant-induced arthritis. Karandish et al [87] used Cu(II)-catalyzed azide-alkyne cycloaddition to design nucleus-targeted, stimuli-responsive polymersomes for the delivery of anticancer drugs to the nuclei of pancreatic cancer cells. In this case, the DEX group was used to improve the transport of the drug carriers to the nuclei via dilation of the nuclear pore.…”
Section: Click Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes were thawed at room temperature. 49 Once the exosomes reached room temperature, 210 mL of exosomes were added dropwise to 1.5 mL of 320 mM mannitol-HEPES buffer (pH 7.4) while stirring. Aer 10 minutes of stirring, pressurized ltered ambient air was bubbled in for 45 minutes.…”
Section: Echogenic Exosomes Preparationmentioning
confidence: 99%